The melanocortin receptors and their accessory proteins - Ramachandrappa, Shwetha; Gorrigan, Rebecca; Clark, Adrian; Chan, Li (Frontiers in Endocrinology, 2013)
The five melanocortin receptors named MC1R-MC5R have diverse physiological roles encompassing pigmentation, steroidogenesis, energy homeostasis and feeding behaviour as well as exocrine function. Since their identification almost 20 years ago much has been learnt about these receptors. As well as interacting with their endogenous ligands the melanocortin peptides, there is now a growing list of important peptides that can modulate the way these receptors signal, acting as agonists, antagonists and inverse agonists. The discovery of MRAPs as a novel accessory factor to the melanocortin receptors provides further insight into the regulation of these important GPCRs.